Reconciliation of Sharia and Reality: Answering Fiqh's Criticism of Sufism Through Al-Baghdadi's Neo-Sufism Paradigm in Contemporary Morocco - Islam, Husein Muhammad Fajrul (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2026)
Throughout the history of Islamic civilization, Sufi circles have often been the target of criticism from certain factions of scholars, particularly jurists. This is fueled by the perception that Sufis tend to set aside the external aspects of Sharia law in favor of prioritizing the inner dimension and abandoning worldly attachments. However, this opinion is not always true. With Morocco as the object of this research, the land of the setting sun can serve as an example and a mecca for the application of Sufism from its inception to the modern era. The modern Sufism of Sheik Junayd Al Baghdadi in Morocco has become an icon and is deeply rooted. The Sufi teachings and assemblies that developed in Morocco eventually became a distinctive Moroccan Islamic tradition and an inseparable part of royal life. The kingdom even officially made Sufi teachings and assemblies a solution to address the problem of religious extremism. Modern Sufism, or neo-Sufism, emerged as an alternative for modern humans and represents a renewal of classical Sufism, which was considered inconsistent with Sharia law. Through its moderate and humanist practice, Sufism is no longer considered a backward religious teaching.